(untitled) (Baghdad Science Journal, 2025)
Citrus fruit contain variety of flavonoids such as Hesperidin (the principal flavonoid in oranges and grapefruit). Hesperidin is found in high concentration in fruit peel of oranges and in substantially lower concentration in juice of these fruits. Hesperidin was extracted from oranges peel by treating the peels with calcium hydroxide. HPLC technique was used to determine hesperidin. Hesperidin was saperated and purified in a purity of about 90.1-95.7% and yield about 1.5 %w/w from oranges peel dry powder. Both hesperidin and oranges peel extract showed significan antibacterial activity. Sensitivity to hesperidin and oranges peel extracts were not similar for the chosen bacteriaCrude orange peel extract gave a various antimicrobial activity agents Gram-positive Bacillus cereus, Staphylococcus aurous, Streptococcus pyogenus sp. and Gram-negative (Escherichia coli, Salmonella typhi) bacteria strains`. The minimum inhibitory concentration (MIC) values against these bacteria ranged from 45-175?g/disc.for crude orange peel extractand 175-450?g/disc for pure hesperidin In comparison to 30?g/disc reference standards ciproflaxacin and impinme.orange peel extract showed significant antimicrobial activity.